Anticipating What May Go Wrong: Implications for Managing Schedule Risk - Love, Peter; Sing, Michael; Wang, Xiangyu; Yung, Ping; Odeyinka, H. (RICS 2012, 2012)
The probability of schedule overruns on construction projects can be ascertained using a 'best fit' probability distribution from an empirical distribution. The statistical characteristics of schedule overruns occurring in 276 Australian construction and engineering projects were analysed. Skewness and kurtosis values reveal that schedule overruns are non-Gaussian. Theoretical probability distributions are then fitted to the schedule overrun data; including the Kolmogorov-Smirnov, Anderson-Darling and Chi-Squared non-parametric tests to determine the 'Goodness of Fit.' A Four Parameter Burr (4P) probability function best describes the behaviour of schedule overruns, provides the best overall distribution fit and is used to calculate the probability of their occurrence. Implications for 1nanaging schedule risk are discussed.